Quantitative Assessment of Erector Spinae Muscles in Patients with Chronic Obstructive Pulmonary Disease. Novel Chest Computed Tomography–derived Index for Prognosis - Tanimura, Kazuya; Sato, Susumu; Fuseya, Yoshinori; Hasegawa, Koichi; Uemasu, Kiyoshi; Sato, Atsuyasu; Oguma, Tsuyoshi; Hirai, Toyohiro; Mishima, Michiaki; Muro, Shigeo (Annals of the American Thoracic Society, 2016)
Loss of skeletal muscle mass and physical inactivity are important manifestations of chronic obstructive pulmonary disease (COPD), and both are closely related to poor prognoses in patients with COPD. Antigravity muscles are involved in maintaining normal posture and are prone to atrophy with inactivity. The erector spinae muscles (ESM) are one of the antigravity muscle groups, and they can be assessed by chest computed tomography (CT). We hypothesized that the cross-sectional area of ESM (ESMCSA) visualized on chest CT images may serve as a predictor of mortality in patients with COPD. This study was part of the prospective observational study undertaken at Kyoto University Hospital. ESMCSA was measured on a single-slice axial CT image at the level of the 12th thoracic vertebra in patients with COPD. The cross-sectional area of the pectoralis muscles (PMCSA) was also measured. We evaluated the relationship between ESMCSA and clinical parameters, including mortality, in patients with COPD. Age- and height-matched smoking control subjects were also evaluated. In total, 130 male patients and 20 smoking control males were enrolled in this study. ESMCSA was significantly lower in patients with COPD than in the smoking control subjects and was significantly correlated with disease severity. There was a significant but only moderate correlation between ESMCSA and PMCSA. ESMCSA was significantly correlated with previously reported prognostic factors, such as body mass index, dyspnea (modified Medical Research Council dyspnea scale score), FEV1 percent predicted value, inspiratory capacity to total lung capacity ratio, and emphysema severity (percentage of the lung field occupied by low attenuation area). Compared with PMCSA, ESMCSA was more strongly associated with mortality in patients with COPD. Stepwise multivariate Cox proportional hazards analysis revealed that, among these known prognostic factors, ESMCSA was the strongest risk factor for mortality (hazard ratio, 0.85; 95% confidence interval, 0.79-0.92; P < 0.001) and mMRC dyspnea scale score was an additional factor (hazard ratio, 2.35; 95% confidence interval, 1.51-3.65; P < 0.001). ESMCSA assessed by chest CT may be a valuable clinical parameter, as ESACSA correlates significantly with physiological parameters, symptoms, and disease prognosis.